(untitled) (Discourse of Law and Administration, 2022)
The subject of the considerations is the presentation of selected solutions, mainly political ones, contained in the Gibraltar Constitution of December 14, 2006, and drawing attention to the numerous legal ties of this area with the British Crown, and then an attempt to establish the legal nature of this territory. Gibraltar is an overseas territory of the United Kingdom, but is treated by the European Union as a British colony. For this reason, it is necessary to reflect on its independence. Gibraltar’s status is complicated.